A kind of anti-cracking composite material for concrete repair and preparation method thereof

By modifying basalt fibers and bentonite, combined with materials such as sodium alginate-based modified fibers, a three-dimensional support net is formed, which solves the problems of poor stability and poor fiber dispersion of existing concrete restoration materials in high-temperature environments, and significantly improves concrete The tensile strength and toughness extend the service life.

CN118812187BActive Publication Date: 2025-01-17SHANDONG BEIRUISI WATERPROOF TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411296362.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-17
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing concrete restoration materials have poor stability in high temperature environments and poor fiber dispersion, resulting in insufficient crack resistance and affecting the service life of concrete.

Method used

The basalt fibers were modified by γ-methacryloyloxypropyltrimethoxysilane, and the bentonite was modified by maleic anhydride. The modified anti-crack fiber was formed by in-situ polymerization, and the sodium alginate-based modification was modified. The combined action of the fibers, hydroxymethylcellulose, sodium dodecylbenzenesulfonate, calcium chloride and calcium oxide form a three-dimensional misdirection support net, enhancing the tensile strength and toughness of concrete.

Benefits of technology

It significantly improves the tensile strength and toughness of concrete, enhances its stability and durability in high-temperature environments, effectively prevents the formation and development of cracks, and extends the service life of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and specifically discloses an anti-cracking composite material for concrete repair and a preparation method thereof. The anti-cracking composite material comprises sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, a water reducer, calcium chloride and calcium oxide. The anti-cracking composite material can be used as a filling material for concrete, is evenly distributed in the concrete, can disperse the directional stress of the concrete, enhance its shrinkage deformation cracking ability, realize the self-repair of concrete cracks, reduce the internal defects of the concrete, thereby improving the microstructure of the concrete, can effectively ensure that the concrete is not easy to crack when subjected to external pressure, blocks the capillary crack channels inside the concrete, reduces the penetration rate of harmful substances such as water, chloride ions and air, and improves its tensile strength and durability. The components in the composite material act synergistically and have excellent concrete crack repairing ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to an anti-cracking composite material for concrete repair and a preparation method thereof. Background Art

[0002] Concrete has the advantages of strong structure and low price, and is the most widely used building material in modern construction projects. However, concrete has low tensile strength, and with the increase of service life, small cracks and local damage are prone to occur inside the concrete. As the cracks and damage gradually increase, they provide channels for the invasion and diffusion of some harmful substances, destroying the internal environment of the concrete, further reducing its durability, greatly affecting the appearance and safety of the building, and shortening the service life of the concrete. Traditional crack repair technologies such as surface repair and crack grouting can alleviate erosion, but the effect is general and the cost is expensive.

[0003] Chinese patent application CN102701635A discloses a nanocomposite expansion anti-cracking agent, whose components and contents are as follows: calcium sulfoaluminate 9.2%-27.5%, calcium aluminate 6.8%-11.2%, calcium hydroxide 7.1%-15.4%, PSP organic silicon powder 4.8%-13.6%, sodium silicate 3.6%-7.5%, ethylenediamine sodium phosphate 0.1%-3.2%, iron powder 0.5%-2.5%, borax 1.0%-3.3%, manganese dioxide 0.1%-0.5%, polypropylene Fiber 0.1%-2.4%, disodium ethylenediaminetetraacetic acid 0.1%-0.8%, sodium tripolyphosphate 1.8%-4.3%, fly ash 15.2%-22.5%, aminophenoxynaphthalene sulfonate 5.3%-11.6%, FP nano polymer 5.1%-8.5%, the expansion generated by the nano-composite expansion anti-cracking agent develops synchronously with the shrinkage of concrete, effectively fills the pores in the concrete, and effectively controls the generation and development of non-structural cracks such as early plastic shrinkage and shrinkage of concrete and cement mortar. However, the patent directly adds the fiber to the concrete, which has the problem of difficult dispersion, and a large number of bubbles are easily generated during the mixing process. The poor adhesion between the fiber and the matrix will reduce its anti-cracking stability. The calcium sulfoaluminate expansion agent added therein reduces the shrinkage of concrete by generating calcium sulfonate, which may decompose at high temperatures, limiting its use in high temperature environments, resulting in a significant reduction in the service life of the concrete. Chinese patent application CN112573866A discloses a self-repairing concrete and its preparation method and application, which includes the following components: cement, sand, crushed stone, polyvinyl alcohol, fly ash, sodium alginate, recycled PP short fibers, water reducer, hydroxymethyl cellulose, anti-cracking fibers, microsilica powder, sodium silicate, deionized water, and water. The recycled PP short fibers and anti-cracking fibers in the self-repairing concrete form a network structure, which can effectively reduce the occurrence of cracks, but the dispersibility between the raw materials is poor and the repair performance is average. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides an anti-cracking composite material for concrete repair and a preparation method thereof, which solves the problem that concrete structures are prone to cracking.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the present invention discloses a method for preparing an anti-cracking composite material for concrete repair, comprising the following steps:

[0008] Step 1: adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, reacting, and after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0009] Step 2: Evenly mix maleic anhydride and acetone, then add bentonite, stir and mix to react, and after the reaction is completed, perform rotary evaporation to obtain olefin-modified bentonite;

[0010] Step 3: Add olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, then add glycidyl methacrylate and an initiator, mix well, heat, and react. After the reaction is completed, wash with deionized water, filter, and vacuum dry at 60° C. for 12 hours to obtain a modified anti-cracking fiber;

[0011] Step 4: adding sodium alginate to deionized water, stirring and mixing evenly, adding modified anti-cracking fiber, stirring and mixing, adjusting the pH to 4-5 with hydrochloric acid solution, heating, reacting, centrifuging after the reaction, washing with deionized water, freeze-drying, and obtaining sodium alginate-based modified fiber;

[0012] Step 5: Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 40-60 minutes, then add calcium chloride and calcium oxide, stir for 15-30 minutes, and obtain an anti-cracking composite material for concrete repair.

[0013] Preferably, in the step 1, the mass ratio of the mixed solvent, basalt fiber and γ-methacryloxypropyltrimethoxysilane is (2400-3000):100:(21-28).

[0014] Preferably, the volume ratio of anhydrous ethanol to deionized water in the mixed solvent in step 1 is 9:1.

[0015] Preferably, the reaction temperature in step 1 is 80-90° C., and the reaction time is 4-6 h.

[0016] Preferably, in step 2, the mass ratio of maleic anhydride, acetone and bentonite is (170-210): (4200-5000): 100.

[0017] Preferably, the reaction temperature in step 2 is 25-35° C., and the reaction time is 12-15 h.

[0018] Preferably, in step three, the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator is 100:(82-105):(40-70):(900-1200):(3600-4800):(15-30):(2-3).

[0019] Preferably, the reaction temperature in step 3 is 75-85° C., and the reaction time is 2-4 h.

[0020] Preferably, the initiator in step three comprises one of azobisisobutyronitrile, benzoyl peroxide and diisopropylbenzene peroxide.

[0021] Preferably, in step 4, the mass ratio of sodium alginate, deionized water and modified anti-cracking fiber is 78-95:450-600:100.

[0022] Preferably, the reaction temperature in step 4 is 60-65° C., and the reaction time is 8-10 h.

[0023] Preferably, the hydrochloric acid solution in step 4 is a 1 mol / L hydrochloric acid aqueous solution.

[0024] Preferably, in step 5, the mass ratio of sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, water reducer, calcium chloride and calcium oxide is 100:(18-25):(2-5):(4-7):(6-9):(2-4):(1-2).

[0025] Preferably, the water reducing agent in step 5 is a polycarboxylate water reducing agent.

[0026] Preferably, an anti-cracking composite material for concrete repair is prepared by the method for preparing the anti-cracking composite material for concrete repair.

[0027] 3. Beneficial technical effects

[0028] In the present invention, γ-methacryloxypropyltrimethoxysilane is used to modify basalt fiber, alkenyl is introduced to obtain alkenyl-modified basalt fiber, maleic anhydride is used to modify bentonite, maleic anhydride reacts with hydroxyl groups on the surface of bentonite, maleic anhydride is ring-opened, alkenyl and carboxyl groups are introduced on the surface of bentonite, and alkenyl-modified bentonite is obtained. Under the action of an initiator, alkenyl-modified basalt fiber, alkenyl-modified bentonite, polypropylene fiber, and glycidyl methacrylate are in-situ polymerized to obtain modified anti-cracking fiber, and epoxy groups are introduced. The epoxy groups on the surface of the modified anti-cracking fiber react with sodium alginate, and hydroxyl groups are introduced after ring opening to obtain sodium alginate-based modified fiber. Sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, a water reducer, calcium chloride, and calcium oxide are stirred and mixed to obtain an anti-cracking composite material for concrete repair.

[0029] Basalt fiber is a new type of inorganic environmentally friendly green high-performance fiber material with excellent mechanical properties, chemical stability and thermal stability. It can effectively improve the tensile strength and toughness of concrete. When concrete is subjected to external forces, it can bear part of the tensile stress to prevent the concrete from cracking prematurely. At the same time, it can refine the micro cracks inside the concrete, reduce the internal defects of the concrete, and play a repairing role. Bentonite has stable chemical properties and good weather resistance. Bentonite has strong water absorption properties. After absorbing water, it forms a dense colloidal structure, which can effectively fill the tiny pores and cracks inside the concrete. At the same time, this colloidal structure has good waterproof properties, preventing moisture and harmful substances from penetrating into the concrete, improving the stability and durability of the concrete, and helping to extend the service life of the concrete. In concrete repair, bentonite can maintain the stability and durability of its performance. Polypropylene fiber has the advantages of high strength, good toughness, chemical resistance and good anti-microbial properties. It can effectively control microcracks caused by factors such as plastic shrinkage, shrinkage and temperature changes of concrete, prevent and inhibit the formation and development of original cracks in concrete, and at the same time increase the toughness of concrete, enabling it to better resist external impact and fatigue, and improve the durability of concrete.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The sodium alginate in the present invention has water-absorbing and swelling properties, can absorb water and swell, and plug cracks. When cracks appear in the concrete matrix, the anti-cracking composite material for repair is added. When water penetrates into the cement matrix, it can be used as a filling material for concrete, realizing self-repair of concrete cracks, and still has excellent strength after repair. The olefin-modified basalt fiber, olefin-modified bentonite and polypropylene fiber are in-situ polymerized, which effectively improves the dispersibility. After reacting with sodium alginate, the two fibers of different lengths work together and overlap each other to form a three-dimensional staggered support network, forming a bridge structure, which is conducive to dispersing the directional stress of concrete and bearing the internal stress caused by concrete shrinkage, thereby enhancing its ability to shrink, deform and crack. It has excellent crack resistance, good toughness and excellent mechanical properties. When added to concrete, it can reduce internal defects of concrete and improve the microstructure of concrete. The composite material can be evenly distributed in concrete, which can effectively ensure that concrete is not easy to crack when subjected to external pressure, block the capillary crack channels inside the concrete, reduce the penetration rate of harmful substances such as water, chloride ions and air, and improve its tensile strength and durability.

[0032] (2) Hydroxypropyl methylcellulose in the present invention can fill the tiny pores and cracks in concrete, reducing the shrinkage and cracking of concrete. Sodium dodecylbenzene sulfonate can react with free calcium ions in concrete to form a dense base material, filling the pores and microcracks inside the concrete, while reducing water penetration and improving the concrete's impermeability. Polycarboxylic acid water reducer can adsorb on the surface of cement and sand in concrete to form a dispersant coating, thereby reducing the water-cement ratio and improving the fluidity of the composite material. It can react with calcium ions to form a coating with high dispersibility, improving the density and fluidity of the composite material, and further improving durability and mechanical properties. Calcium oxide can adjust the pH value in concrete and promote the hydration reaction of cement in concrete. The addition of calcium chloride can promote the continued hydration of cement after the concrete cracks, thereby filling the cracks. After the concrete cracks, moisture in the air enters the cracks, and the calcium ion concentration increases, which can promote the decomposition of calcium ions by calcium hydroxide, increase the calcium ion concentration in the system, and then make the calcium ions react with cement and silicate ions to form solid calcium carbonate and calcium silicate to fill the cracks, thereby playing a role in filling the cracks. The various components in the composite material work synergistically, have excellent concrete crack repair capabilities, and can also improve the durability of concrete. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0034] Example 1

[0035] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0036] Step 1, adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 9:1, and after mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, wherein the mass ratio of the added mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is 2400:100:21, reacting at 80° C. for 6 hours, after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0037] Step 2: Evenly mix maleic anhydride and acetone, and then add bentonite, wherein the mass ratio of maleic anhydride, acetone and bentonite is 170:4200:100, stir and mix, react at 25° C., and react for 15 hours. After the reaction is completed, rotary evaporate to obtain olefin-modified bentonite;

[0038] Step 3, adding olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, and then adding glycidyl methacrylate and initiator azobisisobutyronitrile, wherein the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator azobisisobutyronitrile is 100:82:40:900:3600:15:2, mixing evenly, heating, reacting at 75°C, the reaction time is 4h, after the reaction is completed, washing with deionized water, filtering, and vacuum drying at 60°C for 12h to obtain modified crack-resistant fiber;

[0039] Step 4: Add sodium alginate to deionized water, stir and mix evenly, then add modified anti-cracking fiber, the mass ratio of sodium alginate, deionized water and modified anti-cracking fiber is 78:450:100, stir and mix, adjust the pH to 4 with hydrochloric acid solution, the hydrochloric acid solution is 1 mol / L hydrochloric acid aqueous solution, heat up, react at 60°C, the reaction time is 10 hours, after the reaction is completed, centrifuge, wash with deionized water, freeze-dry, and obtain sodium alginate-based modified fiber;

[0040] Step 5. Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 40 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of the sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 100:18:2:4:6:2:1, stir for 15 minutes, and obtain an anti-cracking composite material for concrete repair.

[0041] Example 2

[0042] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0043] Step 1, adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 9:1, and after mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, wherein the mass ratio of the added mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is 2600:100:24, reacting at 85° C. for 5 hours, after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0044] Step 2: Evenly mix maleic anhydride and acetone, and then add bentonite, wherein the mass ratio of maleic anhydride, acetone and bentonite is 185:4500:100, stir and mix, react at 30°C for 14 hours, and after the reaction is completed, rotary evaporate to obtain olefin-modified bentonite;

[0045] Step 3, adding olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, and then adding glycidyl methacrylate and initiator azobisisobutyronitrile, wherein the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator azobisisobutyronitrile is 100:90:55:1000:4000:20:2.2, mixing evenly, heating, reacting at 80°C, the reaction time is 3h, after the reaction is completed, washing with deionized water, filtering, and vacuum drying at 60°C for 12h to obtain modified anti-cracking fiber;

[0046] Step 4: Add sodium alginate to deionized water, stir and mix evenly, then add modified anti-cracking fiber, the mass ratio of sodium alginate, deionized water and modified anti-cracking fiber is 85:500:100, stir and mix, adjust the pH to 4.5 with hydrochloric acid solution, the hydrochloric acid solution is 1 mol / L hydrochloric acid aqueous solution, heat up, react at 62°C, the reaction time is 9 hours, after the reaction is completed, centrifuge, wash with deionized water, freeze-dry, and obtain sodium alginate-based modified fiber;

[0047] Step 5. Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 45 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of the sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 100:20:3:5:7:2.5:1.4, stir for 20 minutes, and obtain an anti-cracking composite material for concrete repair.

[0048] Example 3

[0049] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0050] Step 1, adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 9:1, and after mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, wherein the mass ratio of the added mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is 2800:100:26, reacting at 85° C. for 5 hours, after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0051] Step 2: Evenly mix maleic anhydride and acetone, and then add bentonite, wherein the mass ratio of maleic anhydride, acetone and bentonite is 200:4800:100, stir and mix, react at 30° C., and react for 14 hours. After the reaction is completed, rotary evaporate to obtain olefin-modified bentonite;

[0052] Step 3, adding olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, and then adding glycidyl methacrylate and initiator azobisisobutyronitrile, wherein the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator azobisisobutyronitrile is 100:98:65:1100:4400:25:2.6, mixing evenly, heating, reacting at 80°C, the reaction time is 3h, after the reaction is completed, washing with deionized water, filtering, and vacuum drying at 60°C for 12h to obtain modified anti-cracking fiber;

[0053] Step 4: Add sodium alginate to deionized water, stir and mix evenly, then add modified anti-cracking fiber, the mass ratio of sodium alginate, deionized water and modified anti-cracking fiber is 90:550:100, stir and mix, adjust the pH to 4.5 with hydrochloric acid solution, the hydrochloric acid solution is 1 mol / L hydrochloric acid aqueous solution, heat up, react at 62°C, the reaction time is 9 hours, after the reaction is completed, centrifuge, wash with deionized water, freeze-dry, and obtain sodium alginate-based modified fiber;

[0054] Step 5. Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 45 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of the sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 100:20:3:5:7:2.5:1.4, stir for 20 minutes, and obtain an anti-cracking composite material for concrete repair.

[0055] Example 4

[0056] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0057] Step 1: Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 55 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of the sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 100:24:4:6:8:3.5:1.8, stir for 25 minutes, and obtain an anti-cracking composite material for concrete repair.

[0058] The preparation method of the sodium alginate-based modified fiber is the same as the preparation method of the sodium alginate-based modified fiber in Example 3.

[0059] Example 5

[0060] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0061] Step 1, adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 9:1, and after mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, wherein the mass ratio of the added mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is 3000:100:28, reacting at 90° C. for 4 hours, after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0062] Step 2: Evenly mix maleic anhydride and acetone, and then add bentonite, wherein the mass ratio of maleic anhydride, acetone and bentonite is 210:5000:100, stir and mix, react at 35° C., and react for 12 hours. After the reaction is completed, rotary evaporate to obtain olefin-modified bentonite;

[0063] Step 3, adding olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, and then adding glycidyl methacrylate and initiator azobisisobutyronitrile, wherein the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator azobisisobutyronitrile is 100:105:70:1200:4800:30:3, mixing evenly, heating, reacting at 85°C, the reaction time is 2h, after the reaction is completed, washing with deionized water, filtering, and vacuum drying at 60°C for 12h to obtain modified crack-resistant fiber;

[0064] Step 4: Add sodium alginate to deionized water, stir and mix evenly, then add modified anti-cracking fiber, the mass ratio of sodium alginate, deionized water and modified anti-cracking fiber is 95:600:100, stir and mix, adjust the pH to 5 with hydrochloric acid solution, the hydrochloric acid solution is 1 mol / L hydrochloric acid aqueous solution, heat up, react at 65°C, the reaction time is 8 hours, after the reaction is completed, centrifuge, wash with deionized water, freeze-dry, and obtain sodium alginate-based modified fiber;

[0065] Step 5. Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 60 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of the sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 100:25:5:7:9:4:2, stir for 30 minutes, and obtain an anti-cracking composite material for concrete repair.

[0066] Comparative Example 1

[0067] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0068] Step 1, adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 9:1, and after mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, wherein the mass ratio of the added mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is 2800:100:26, reacting at 85° C. for 5 hours, after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0069] Step 2: Evenly mix maleic anhydride and acetone, and then add bentonite, wherein the mass ratio of maleic anhydride, acetone and bentonite is 200:4800:100, stir and mix, react at 30° C., and react for 14 hours. After the reaction is completed, rotary evaporate to obtain olefin-modified bentonite;

[0070] Step 3, adding olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, and then adding glycidyl methacrylate and initiator azobisisobutyronitrile, wherein the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator azobisisobutyronitrile is 100:98:65:1100:4400:25:2.6, mixing evenly, heating, reacting at 80°C, the reaction time is 3h, after the reaction is completed, washing with deionized water, filtering, and vacuum drying at 60°C for 12h to obtain modified anti-cracking fiber;

[0071] Step 4: Evenly mix sodium alginate, modified anti-cracking fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and water reducer, stir and mix for 55 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of sodium alginate, modified anti-cracking fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 47:53:24:4:6:8:3.5:1.8, stir for 25 minutes, and obtain an anti-cracking composite material for concrete repair.

[0072] Comparative Example 2

[0073] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0074] Step 1, adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water in the mixed solvent is 9:1, and after mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, wherein the mass ratio of the added mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is 2800:100:26, reacting at 85° C. for 5 hours, after the reaction is completed, filtering, washing with deionized water, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber;

[0075] Step 2: Evenly mix maleic anhydride and acetone, and then add bentonite, wherein the mass ratio of maleic anhydride, acetone and bentonite is 200:4800:100, stir and mix, react at 30° C., and react for 14 hours. After the reaction is completed, rotary evaporate to obtain olefin-modified bentonite;

[0076] Step 3: Evenly mix sodium alginate, olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite and deionized water, add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and water reducer, stir and mix for 55 minutes, then add calcium chloride and calcium oxide, wherein the mass ratio of sodium alginate, olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, polycarboxylic acid water reducer, calcium chloride and calcium oxide is 47:20:20:13:24:4:6:8:3.5:1.8, stir for 25 minutes, and obtain an anti-cracking composite material for concrete repair.

[0077] Comparative Example 3

[0078] A method for preparing an anti-cracking composite material for concrete repair comprises the following steps:

[0079] Step 1: Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, and stir and mix for 55 minutes, wherein the mass ratio of the sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and polycarboxylate water reducer is 100:24:4:6:8, to obtain an anti-cracking composite material for concrete repair.

[0080] The preparation method of the sodium alginate-based modified fiber is the same as the preparation method of the sodium alginate-based modified fiber in Example 3.

[0081] The basalt fiber used in the embodiments and comparative examples of the present invention was purchased from Zhejiang Shijin Company, with a length of 6 mm and a diameter of 13 μm; bentonite was purchased from Merck Sigma-Aldrich Company (USA), with an average particle size of ≤25 μm and a purity of ≥98%; polypropylene fiber was purchased from Beijing Wantuming Technology Co., Ltd., with a diameter of 20 μm and a product number of 20200405; hydroxymethyl cellulose was purchased from Hebei Renqiu Xingle Chemical Co., Ltd., with a brand of Xingle and a model of IMH8; sodium alginate was chemically pure and was purchased from Sinopharm Chemical Reagent Co., Ltd.; the water reducer was a polycarboxylic acid water reducer purchased from Tianjin Feilong Concrete Admixture Co., Ltd., with a model of TFL-2 polycarboxylic acid high-performance water reducer; other raw materials and reagents not specified are commercially available.

[0082] The composite materials for concrete repair prepared in Examples 1-5 and Comparative Examples 1-3 were respectively stirred and mixed with cement, fly ash, sand, gravel and water, wherein the mass ratio of the composite material for concrete repair, cement, fly ash, sand, gravel and water was 14:45:85:162:235:150, and the corresponding concretes were obtained, which were respectively recorded as samples 1-8. The concrete obtained by mixing cement, fly ash, sand, gravel and water in a mass ratio of 45:85:162:235:150 was used as a blank sample, and relevant tests were performed on samples 1-8 and the blank sample.

[0083] The cement was purchased from Jiangnan Onoda Cement Co., Ltd., P·Ⅱ52.5 cement, density 3.17g / cm 3 , specific surface area 388m 2 / kg; fly ash was purchased from the fly ash plant of Shenyang Power Plant and was Grade II fly ash; sand was fine sand purchased from Shanghai Huanyu Building Engineering Materials Co., Ltd. with a fineness modulus of 2.0 and industrial grade; the particle size of gravel was 6-15mm.

[0084] The compressive strength of samples 1-8 and blank samples after standard curing for 7 days and 28 days, as well as the compressive strength after re-curing for 7 days and 28 days after cracking, were tested. The test method refers to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete"; the impermeability grade of samples 1-8 and blank samples was tested, referring to GB 50108-2008 "Technical Specifications for Waterproofing of Underground Engineering". The relevant test results are shown in Table 1:

[0085] Table 1

[0086] Test items 7d compressive strength (MPa) 28d compressive strength (MPa) Impermeability grade After cracking, curing to 7d compressive strength (MPa) After cracking, curing to 28d compressive strength (MPa) Sample 1 32.5 48.7 P8 35.7 50.1 Sample 2 33.8 51.3 P9 37.2 53.5 Sample 3 34.1 52.0 P9 37.8 54.6 Sample 4 34.7 53.6 P10 38.2 56.7 Sample 5 33.5 50.8 P9 36.9 52.9 Sample 6 31.9 47.5 P8 34.5 49.2 Sample 7 30.8 46.8 P8 33.1 48.1 Sample 8 32.1 48.0 P7 34.9 49.3 Blank 28.9 44.5 P6 27.3 40.1

[0087] According to the test results of Table 1, it can be seen that the concrete corresponding to samples 1-5 in the present invention has excellent compressive strength compared with the blank sample, and the impermeability is excellent. After the concrete cracks, when it is re-cured to the corresponding age, the secondary compressive strength is improved, and the crack resistance is excellent. Mainly due to the good bonding of the composite material with the concrete matrix at the crack, the overall strength of the concrete matrix is ​​further improved. In sample 6, sodium alginate and modified crack-resistant fiber are directly mixed, and the compressive strength is reduced. In sample 7, sodium alginate, olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite are directly added to replace sodium alginate-based modified fiber, and the dispersibility between the raw materials deteriorates, the compatibility is poor, the compressive strength is greatly reduced, and the repair ability deteriorates. Calcium chloride and calcium oxide are not added in sample 8, and the impermeability and repair performance of the concrete deteriorate, and the 7d compressive strength and 28d compressive strength are both deteriorated.

[0088] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing an anti-cracking composite material for concrete repair, characterized in that: The following steps are involved: Step 1: adding basalt fiber to a mixed solvent of anhydrous ethanol and deionized water, mixing evenly, adding γ-methacryloxypropyltrimethoxysilane, stirring and mixing, reacting, and after the reaction is completed, filtering, washing, and vacuum drying at 60° C. for 6 hours to obtain olefin-modified basalt fiber; Step 2: Evenly mix maleic anhydride and acetone, then add bentonite, stir and mix to react, and after the reaction is completed, perform rotary evaporation to obtain olefin-modified bentonite; Step 3: Add olefin-modified basalt fiber, polypropylene fiber, and olefin-modified bentonite to a mixed solution of toluene and deionized water, then add glycidyl methacrylate and an initiator, mix well, heat, react, wash, filter, and vacuum dry at 60° C. for 12 hours after the reaction is completed to obtain a modified anti-cracking fiber; Step 4: adding sodium alginate to deionized water, stirring and mixing evenly, adding modified anti-cracking fiber, stirring and mixing, adjusting the pH to 4-5 with hydrochloric acid solution, heating, reacting, centrifuging, washing, and freeze-drying after the reaction to obtain sodium alginate-based modified fiber; Step 5: Evenly mix the sodium alginate-based modified fiber and deionized water, then add hydroxymethyl cellulose, sodium dodecylbenzene sulfonate and a water reducer, stir and mix for 40-60 minutes, then add calcium chloride and calcium oxide, stir for 15-30 minutes, and obtain an anti-cracking composite material for concrete repair.

2. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: In the step 1, the mass ratio of the mixed solvent, basalt fiber, and γ-methacryloxypropyltrimethoxysilane is (2400-3000):100:(21-28), the volume ratio of anhydrous ethanol and deionized water in the mixed solvent is 9:1, the reaction temperature is 80-90° C., and the reaction time is 4-6 hours.

3. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: In the step 2, the mass ratio of maleic anhydride, acetone and bentonite is (170-210): (4200-5000):

100.

4. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: In the step three, the mass ratio of olefin-modified basalt fiber, polypropylene fiber, olefin-modified bentonite, toluene, deionized water, glycidyl methacrylate and initiator is 100: (82-105): (40-70): (900-1200): (3600-4800): (15-30): (2-3).

5. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: The reaction temperature in step 3 is 75-85° C., and the reaction time is 2-4 hours.

6. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: The initiator in step three includes one of azobisisobutyronitrile, benzoyl peroxide and diisopropylbenzene peroxide.

7. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: In the step 4, the mass ratio of sodium alginate, deionized water and modified anti-cracking fiber is (78-95): (450-600):

100.

8. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: The reaction temperature in step 4 is 60-65° C., and the reaction time is 8-10 h.

9. The method for preparing a crack-resistant composite material for concrete repair according to claim 1, characterized in that: In the step 5, the mass ratio of sodium alginate-based modified fiber, deionized water, hydroxymethyl cellulose, sodium dodecylbenzene sulfonate, water reducer, calcium chloride and calcium oxide is 100: (18-25): (2-5): (4-7): (6-9): (2-4): (1-2).

10. An anti-cracking composite material for concrete repair prepared by the method for preparing an anti-cracking composite material for concrete repair according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nanometer composite type expansion anti-cracking waterproofing agent

    CN102701635A

  • Self-repairing concrete as well as preparation method and application thereof

    CN112573866A

  • Cement-based composite material

    CN107365116A

  • Modified bentonite impermeable material as well as preparation method and application thereof

    CN112551944A